The Effect of Earnings Pershare (EPS), Return on Equity (ROE) and Net Profit Margin (NPM) on Stock Returns Before and During the Covid-19 Pandemic in the Transportation Sub-Sector Listed on the Indonesian Stock Exchange (BEI) - Erlangga Saputra; Amiruddin Amiruddin; Lia Uzliawati (International Journal of Economics, Commerce, and Management, 2025)
The purpose of this study was to determine whether there is an effect of Earning Per Share (EPS), Return on Equity (ROE) and Net Profit Margin (NPM) on Stock Returns in the transportation sub-sector listed on the Indonesia Stock Exchange for the 2018-2021 period.The research method used is quantitative method, and uses a research population of 9 transportation companies. The sample technique used is purposive sampling method, the data in this study are financial statements in the form of ratios that represent each research variable and are processed using the SPSS Version 26 instrument measuring tool, the results of the t test (partial) Earning Per Share (EPS) hypothesis test research obtained that the tcount value < t table (0.559 < 2.036), with a sig value of (0.580 > 0.05) then H0 is accepted and HI is rejected. The t test (persial) Return On Equity (ROE) obtained that the value of tcount < ttable (-0.377 > 0.05), with a sig value of (0.580 > 0.05), then H0 is accepted and HI is rejected (-2.036) with a sig value of (0.709> 0.05), then H0 is accepted and HI is rejected. The t test (persial) Net Profit Margin (NPM) obtained tcount < ttable (0.952 < 2.036) with a sig value of (0.348 > 0.05), then H0 is accepted and HI is rejected, Based on these results it can be concluded that Earning Per Share (EPS), Return On Equity (ROE) and Net Profit Margin (NPM) have no significant negative effect on Stock Returns.